ANALISIS MANAJEMEN RISIKO TEKNOLOGI INFORMASI MENGGUNAKAN COBIT 5 (STUDI KASUS: PT GLOBAL INFOTECH) - Prilly Peshaulia Thenu; Agustinus Fritz Wijaya; Christ Rudianto (Jurnal Ilmiah Terpadu Universitas Bina Darma, 2020)
PT Global Infotech Solutions is a company engaged in the field of IT solutions. The company does business by becoming an IT consultant or providing solutions to every customer who has problems including software, hardware and networking systems. Information technology is supporting business in the company, so IT risks can occur at any time. Seeing this problem, management / managing risk is the right way to minimize the potential losses incurred. Therefore, in this study the authors conducted risk management of information technology using COBIT 5. The measurement results of capability level that PT Global Infotech Solutions is at level 1 in managing risk according to the APO12 domain. There are several recommendations given so that risk management can run well.